(untitled) (Journal of Monno Medical College, 2026)
Acinetobacter baumannii is an important opportunistic pathogen and is often involved in various nosocomial infections, such as bacteremia, urinary tract infection, surgical site infection, and nosocomial and ventilator associated pneumonia, especially in patients admitted to ICU. Acinetobacter baumannii is notable for its remarkable innate and acquired resistance to multiple antimicrobial classes, including extended-spectrum cephalosporins and carbapenems. Resistance to carbapenems is the most concerning, as carbapenems have a potent activity against Acinetobacter spp and are often used as a last resort for the treatment of infections due to multidrug resistant Acinetobacter baumannii isolates. In developing countries also, the misuse and underuse of antimicrobials due to lack of awareness of patients, medical workers and financial problems emerged the antimicrobial resistant strains. Due to rapid globalization of human population by travel and other factor these resistant strains spread easily between developed and developing countries making it a global problem. Journal of Monno Medical College, June, 2025; 11(1) : 65-76